“Smashing through barriers”? A multimodal critical discourse analysis of media representations of hearing loss and D/deafness - Sophie Fawcett-Jones; Emma Putland; Sian Calvert; Emma Broome; Helen Henshaw; Tom Dening; Clare Burgon; Eithne Heffernan (PLoS ONE, 2026)
Hearing loss (HL) is a prevalent condition that can substantially impact quality of life. Hearing aids can benefit people living with HL, yet many delay seeking treatment. This may be due to limited public awareness of HL and the stigma surrounding HL and hearing aids. The media can significantly shape public perceptions of HL and D/deafness, and there have been calls for improved media portrayals of HL and D/deafness. This study examined how British newspapers represent HL and D/deafness both visually and textually, and whether these representations reiterate and/or challenge stigma. This qualitative study used multimodal critical discourse analysis (MCDA) guided by stigma theory and the Visual Discourses of Disability framework. Public contributors living with HL or D/deafness were consulted. A Nexis database search retrieved 7,173 articles about HL or D/deafness from 2022–2023. A random sample, extracted from the 200 most relevant articles, was screened. Three key themes were identified: (1) representing social progress, including technological advancements and societal roles for people with HL or D/deaf people, (2) the lack of diverse narratives and perspectives, including the absence of older adults, and (3) the stigma and social barriers associated with living in a hearing-orientated world, including tensions regarding whether HL should be (in)visible. Combined, this suggests that the overall social progress narrative is challenged by continued stigmatisation and inadequate diversity. This research was a novel application of MCDA to representations of HL and D/deafness, which focused on British newspapers. Further efforts are needed to improve these representations, particularly representations of older adults. Future research should apply MCDA to representations of HL and D/deafness in other contexts. The findings have important implications for academics in discourse and disability studies, and for all those who communicate with the public about hearing loss, including researchers, clinicians, public health officials, charities, and the media.